2015
DOI: 10.1242/jcs.163675
|View full text |Cite
|
Sign up to set email alerts
|

Cell competition in mouse NIH3T3 embryonic fibroblasts controlled by Tead activity and Myc

Abstract: Cell competition is a short-range communication originally observed in Drosophila. Relatively little is known about cell competition in mammals or in non-epithelial cells. Hippo signaling and its downstream transcription factors of the Tead family, control cell proliferation and apoptosis. Here, we established an in vitro model system that shows cell competition in mouse NIH3T3 embryo fibroblast cells. Co-culture of Tead-activity-manipulated cells with normal (wild-type) cells caused cell competition. Cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 52 publications
(88 reference statements)
2
24
0
Order By: Relevance
“…In Drosophila , mutations in the components of the tumor‐suppressor Hippo pathway, such as expanded , fat , salvador , hippo , warts , and mats , turned cells to be supercompetitors that eliminate surrounding wild‐type cells (Tyler et al., ). Supercompetition by Hippo pathway mutant cells was also observed in cultured mammalian fibroblast cells (Mamada, Sato, Ota, & Sasaki, ). Importantly, the transcriptional co‐activator Yorkie, a downstream of effector of the Hippo pathway, induces myc expression (Neto‐Silva, De Beco, & Johnston, ), suggesting that Hippo‐mediated supercompetition could be driven by Myc‐induced cell competition.…”
Section: Selection Of Fitter Cells: Minute or Myc‐induced Cell Competmentioning
confidence: 71%
See 1 more Smart Citation
“…In Drosophila , mutations in the components of the tumor‐suppressor Hippo pathway, such as expanded , fat , salvador , hippo , warts , and mats , turned cells to be supercompetitors that eliminate surrounding wild‐type cells (Tyler et al., ). Supercompetition by Hippo pathway mutant cells was also observed in cultured mammalian fibroblast cells (Mamada, Sato, Ota, & Sasaki, ). Importantly, the transcriptional co‐activator Yorkie, a downstream of effector of the Hippo pathway, induces myc expression (Neto‐Silva, De Beco, & Johnston, ), suggesting that Hippo‐mediated supercompetition could be driven by Myc‐induced cell competition.…”
Section: Selection Of Fitter Cells: Minute or Myc‐induced Cell Competmentioning
confidence: 71%
“…In Drosophila, mutations in the components of the tumorsuppressor Hippo pathway, such as expanded, fat, salvador, hippo, warts, and mats, turned cells to be supercompetitors that eliminate surrounding wild-type cells (Tyler et al, 2007). Supercompetition by Hippo pathway mutant cells was also observed in cultured mammalian fibroblast cells (Mamada, Sato, Ota, & Sasaki, 2015). Importantly, Minute cell competition (Akai, Igaki, & Ohsawa, 2018).…”
Section: Other Types Of Cell Competition That Select Fitter Cellsmentioning
confidence: 99%
“…The YAP (5SA) mutant protein, in which these five key Ser residues are replaced with Ala, becomes constitutively active. In mouse fibroblast NIH3T3 cells, cell competition resulting in apoptosis was reportedly dependent on TEAD activity (Mamada, Sato, Ota, & Sasaki, ). We subsequently showed that MDCK cells and mouse hepatocytes also undergo YAP‐induced competition (Chiba et al, ; Miyamura et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…When transformed cells establish themselves beside normal epithelial cells, the latter are capable of recognizing the invaders and killing or eliminating them without the aid of the immune response (18). Fibroblasts also have the ability to win such cell competitions (19). Thus, defining the mechanisms underlying cell competition may increase our understanding of normal embryogenesis, tumor elimination and progression, and transplantation medicine.…”
mentioning
confidence: 99%
“…However, the situation is variable in mammals. When mouse nonepithelial cells with low TEAD activity are cocultured with cells with high TEAD activity, the latter become the winners (19). In contrast, Madin-Darby canine kidney (MDCK) cells that overexpress active YAP1 become losers in competition with WT cells and are removed by apical extrusion (38).…”
mentioning
confidence: 99%